(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Bovine brucellosis is an enduring and formidable challenge in Bangladesh. In this first comprehensive review, we explored the historical, current, and future perspectives of bovine brucellosis outbreaks in Bangladesh. Data spanning from 1984 to 2023 regarding bovine brucellosis in Bangladesh were gathered from literature, reviews, conference papers, and online reports using various search engines and software tools. We considered 29 published documents and analyzed them thoroughly to evaluate the current status of bovine brucellosis for the present comprehensive review. We also suggest policy and other frameworks to mitigate and control the disease on a national scale. Bovine brucellosis in Bangladesh affects various livestock and poses economic burdens due to reduced milk and meat production with potential risks to human health. Over the past decade (2013-2023), the ruminant population in Bangladesh has increased substantially (between 1.46 and 26.95 million individuals), with goats showing the most significant growth, while financial losses due to bovine brucellosis have risen steadily, emphasizing its economic impact (basis on species between Euro currency 12.824 and 298.272). This review highlights brucellosis prevalence, diagnostic challenges, and traditional management practices contributing to its spread. Our findings indicate that bovine brucellosis was reported and prevalent in mild to severe forms across 26 districts of Bangladesh. Bangladesh has initiated measures such as vaccination and awareness campaigns, but effective control remains challenging due to diverse farming systems and resource constraints. A one-health approach is advocated for future strategies, emphasizing community engagement and multidisciplinary efforts to address the complex challenges posed by bovine brucellosis in Bangladesh, ultimately aiming to safeguard livestock health, public health, and economic stability. J. Adv. Vet. Anim. Res., 11(4): 888–913, December 2024 http://doi.org/10.5455/javar.2024.k840